2′‐O, 4′‐C‐Methylene‐Bridged Nucleic Acids Stabilize Metal‐Mediated Base Pairing in a DNA Duplex. (18th October 2018) - Nakagawa, Osamu; Fujii, Akane; Kishimoto, Yuki; Nakatsuji, Yusuke; Nozaki, Natsumi; Obika, Satoshi
Abstract: The 2′‐ O, 4′‐ C ‐methylene‐bridged or locked nucleic acid (2′, 4′‐BNA/LNA), with an N‐type sugar conformation, effectively improves duplex‐forming ability. 2′, 4′‐BNA/LNA is widely used to improve gene knockdown in nucleic acid based therapies and is used in gene diagnosis. Metal‐mediated base pairs (MMBPs), such as thymine (T)‐Hg II ‐T and cytosine (C)‐Ag I ‐C have been developed and used as attractive tools in DNA nanotechnology studies. This study aimed to investigate the application of 2′, 4′‐BNA/LNA in the field of MMBPs. 2′, 4′‐BNA/LNA with 5‐methylcytosine stabilized the MMBP of C with Ag I ions. Moreover, the 2′, 4′‐BNA/LNA sugar significantly improved the duplex‐forming ability of the DNA/DNA complex, relative to that by the unmodified sugar. These results suggest that the sugar conformation is important for improving the stability of duplex‐containing MMBPs. The results indicate that 2′, 4′‐BNA/LNA can be applied not only to nucleic acid based therapies, but also to MMBP technologies. Abstract : Sugar, sugar ! 2′‐ O, 4′‐ C ‐methylene‐bridged or locked nucleic acid (2′, 4′‐BNA/LNA) bearing 5‐methylcytosine forms a metal‐mediated base pair with Ag I ions. The 2′, 4′‐BNA/LNA sugar significantly improves the duplex‐forming ability of the DNA/DNA complex compared with that of the unmodified sugar.